Effects of drying pattern on aflatoxin in stored paddy rice - Masood, S; Nisa, Alim un; Hina, S; Ahmad, I (Bangladesh Journal of Scientific and Industrial Research, 2018)
This study was done to evaluate the impact of drying pattern on the accumulation of aflatoxin in paddy rice during storage. Two drying pattern includes, 1) single step drying to reduced the moisture content of paddy rice 11-12 % within 6 hours and stored for long time; and 2) two steps drying to reduce the moisture up to 18%, in its first step and stored for short term (2 weeks) and in the second step, dried again to reduce the moisture content up to 11-12% and stored for longer time, with twenty five different paddy rice samples having moisture content ranging from 24-22 % were evaluated for the accumulation of aflatoxins in paddy rice during storage. In addition, this study also evaluated the best drying method that can control the accumulation of aflatoxin during prolong storage. The study results revealed that one step drying is safer than that of two steps drying in accumulating aflatoxins in paddy rice during 210 days of storage. The maximum total aflatoxins (B1, B2, G1,G2) was recorded as 27 ppb in paddy rice sample in two steps drying process, on the other hand, non-detectable level or <10 ppb level of aflatoxins was recorded in all the 25 paddy rice s amples analyzed. Bangladesh J. Sci. Ind. Res.53(4), 253-258, 2018